2005
DOI: 10.1207/s15324796abm3002_10
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences and advance care planning at end of life: The role of ethnicity and spiritual coping in cancer patients

Abstract: It was found that patients with cancer who used spiritual coping to a greater extent were less likely to have a living will and more likely to desire life-sustaining measures. If efforts aimed at improving end-of-life care are to be successful, they must take into account the complex interplay of ethnicity and spirituality as they shape patients' views and preferences around end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
158
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 40 publications
17
158
2
Order By: Relevance
“…[14][15][16][17][18][19][20] Formal evaluation of these proposed mediators is important because finding a significant mediator could provide a starting point for a targeted intervention to reduce racial/ethnic differences in ACP, whereas finding a lack of mediation would encourage researchers to search for other potential mediating factors.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Formal evaluation of these proposed mediators is important because finding a significant mediator could provide a starting point for a targeted intervention to reduce racial/ethnic differences in ACP, whereas finding a lack of mediation would encourage researchers to search for other potential mediating factors.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Primary barriers indeed include greater mistrust of the health care system, as well as lower knowledge about advance care planning, greater valuation of communal decision making over individual autonomy, and specific spiritual beliefs in African Americans compared to other groups. 1,2 Informed by the knowledge of these known barriers and recognizing that the church is a critical social and valueconveying nexus within the African American community, I assembled a team of community and academic partners, and designed a study that aims to develop and pilot an advance care planning guideline for elderly, churchgoing African Americans in Los Angeles, California. This communitypartnered participatory research project engages pastors and church leaders and trains them in effective techniques to facilitate discussions on advance care planning options within their congregations.…”
mentioning
confidence: 99%
“…5 Prior studies showing ethnic cultural differences over advance care planning, life support, and other aspects of dying further supported our assumption. 3,8,[10][11][12] Our interview study revealed occasional beliefs that may characterize Americans in general, some beliefs that may characterize only certain ethnic groups or genders, and many beliefs that may characterize only particular individuals.…”
Section: Discussionmentioning
confidence: 89%
“…We assumed that culture-the values a group uses to interpret shared experiences and transmits across generations 2,3 -influences those beliefs. 1,[4][5][6][7][8][9][10] We reasoned that, because death is a universal human experience, every culture must address its meaning. 5 Prior studies showing ethnic cultural differences over advance care planning, life support, and other aspects of dying further supported our assumption.…”
Section: Discussionmentioning
confidence: 99%